Changes in the lipid profile of elite basketball and soccer players after a match - Apostolidis, N.; Bogdanis, G.C.; Kostopoulos, N.; Souglis, A.; Papadopoulos, C. (Research in Sports Medicine, 2014)
The lipid profile of elite basketball and soccer athletes was evaluated and compared with that of inactive individuals. Total cholesterol (T-C), low and high density lipoprotein cholesterol (LDL-C and HDL-C), and triglyceride (TG) concentration were measured in the morning and after a soccer or a basketball match. All parameters of lipid profile measured at a fasted and resting state, except HDL-C, were lower in the athletes compared with the controls (p < 0.01). The soccer match resulted in a greater decrease in TG (78.3 ± 6.7 to 70.7 ± 6.3, p < 0.01), T-C (179.3 ± 10.7 to 171.6 ± 9.6, p < 0.01), LDL-C (110.9 ± 8.9 to 103.5 ± 7.5, p < 0.01) compared with the basketball match that resulted only in a decrease in LDL-C (126.8 ± 9.5 to 117.3 ± 9.1, p < 0.01) and an increase in HDL-C that was similar to that observed after the soccer match (9-12%). These findings support the beneficial effects of basketball and soccer on cardiovascular health. © 2013 © Taylor & Francis Group, LLC.
Keywords: Cholesterol; Exercise; training; Triglycerides